Seasonal variability of a conditional stability constant and the characterization of sedimentary humic substances from typical agricultural and urban areas - Pantano, Glaucia [UNESP]; Tadini, Amanda Maria [UNESP]; Bisinoti, Marcia Cristina [UNESP]; Moreira, Altair Benedito [UNESP] (Springer, 2014)
Brazil is the largest producer of sugarcane in the world. This extensive production of sugarcane has changed the use and form of Brazilian soil, causing changes in the structural characteristics of humic substances (HS). In this context, the main objective of this study was to evaluate the effect of seasonality on a conditional stability constant (Kc) of the complexes HS-Cu (II) and HS-Cr (III) from the HS of urban and agricultural regions, with an emphasis on sugarcane culture.The study was conducted in the northwestern region of the state of So Paulo, which is the leading producer of sugar and ethanol in the country and is the region with the lowest percentage of riparian vegetation (3 %). Sediments were sampled during the rainy and dry seasons at four locations: (1) a typical agricultural area, (2) an urban area, (3) a sugarcane cultivation area, (4) and an area that receives the entire pollutant load from the hydrographic basin. The HS were extracted and characterized using conventional techniques. The Kc of the HS with copper (Cu) and chromium (Cr) ions was determined by fluorescence suppression employing the Stern-Volmer model.Kc values were higher in the rainy seasons for HS-Cu (II) and HS-Cr (III). The highest value of Kc for the HS with Cu (1.23) and Cr (5.2 x 10(-1)) ions was found during the rainy season in the area receiving the pollutant load from the basin and in the typical area of sugarcane cultivation, respectively. All of the FTIR spectra showed characteristic bands of HS, and the values of the E-4/E-6 ratio confirmed the presence of more aromatic groups. An elemental analysis and molecular fluorescence spectra in the emission mode confirmed that the HS from the agricultural area and sugarcane culture area mostly exhibited characteristics of humic acids and that the HS from the urban area and the area receiving the pollutant load from the basin had a mixture of humic and fulvic acids.We can conclude that HS-metal complexes from the area that received the entire load of pollutants from the watershed and the typical area of sugarcane culture showed the highest stability among the study areas. The Kc values found in the basin were lower than those previously obtained by several studies that were performed in other locations. The HS obtained in rainy season had more aromatic groups in the HS structure, and the HS from the sugarcane area presented more characteristics of humic acids.
Keywords: Characterization; Conditional stability constant; E-4/E-6 ratio; Humic substances; Molecular fluorescence; Sugarcane